Antimicrobial stewardship programs: mandatory for all ICUs - Kollef, Marin H (BioMed Central, 2012)
Antimicrobial stewardship involves a multifaceted approach aimed at combating the emergence of antibiotic resistance, improving patient outcomes, and controlling healthcare costs by optimizing antimicrobial use. Therefore, stewardship is of great importance and relevance in the ICU. The rapid pace of escalating antibiotic resistance and the widespread use of antibiotics in critical care require that stewardship programs be routinely employed in the ICU setting.